Waves that Appear From Nowhere: Complex Rogue Wave Structures and Their Elementary Particles - Akhmediev, Nail (Frontiers in Physics, 2021)
The nonlinear Schroedinger equation (NLSE) has wide range of applications in physics with spatial scales that vary from microns to kilometres. Consequently, its solutions are also universal and can be applied to water waves, optics, plasma and Bose-Einstein condensate. The most remarkable solution presently known as the Peregrine solution describes waves that appear from nowhere. This solution describes unique events localised both in time and in space. Following the language of mariners they are called ‘rogue waves’. As thorough mathematical analysis shows, these waves have properties that differ them from any other nonlinear waves known before. Peregrine waves can serve as ‘elementary particles’ in more complex structures that are also exact solutions of the NLSE. These structures lead to specific patterns with various degrees of symmetry. Some of them resemble ‘atomic like structures’. The number of particles in these structures is not arbitrary but satisfies strict rules. Similar structures may be observed in systems described by other equations of mathematical physics: Hirota equation, Davey-Stewartson equations, Sasa-Satsuma equation, generalised Landau-Lifshitz equation, complex KdV equation and even the coupled Higgs field equations describing nucleons interacting with neutral scalar mesons. This means that the ideas of rogue waves enter nearly all areas of physics including the field of elementary particles.